Niki Goldschmidt : A Life in Canadian Music - Setterfield, Gwenlyn (Book collections on Project MUSE., 2003)
"Niki Goldschmidt is central to the story of Canada's international musical presence in the second half of the twentieth century. He is well known as the organizer of the great Bach International Piano Competition as well as three immense choral festivals, as a founding director of the Guelph Spring Festival and the Algoma Fall Festival, and for heading the Performing Arts Division of the Centennial Commission in 1967." "In her biography, Gwenlyn Setterfield weaves the captivating story of Goldschmidt's life, following his career as conductor, teacher, and artistic director, from his upbringing in the former Austro-Hungarian Empire to the present day. She recounts his accomplishments, including his involvement in the founding of Canada's first opera school, the creation of festivals in Vancouver, Guelph, Algoma, and Toronto, and productions and tours across the country." "Setterfield illustrates Niki's boundless enthusiasm for Canada's musical potential and his unfailing sense of quality. Whether it was a children's production marking the fiftieth anniversary of the United Nations, or a piano competition celebrating the Bach bicentennial and Glenn Gould, Niki has embraced every project with optimism and respect for his performers and his audiences. The story of Niki Goldschmidt's long life and continuing work is in large part the story of Canada's artistic coming of age."--Jacket.